2023
DOI: 10.1101/2023.03.14.23287194
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detecting post-stroke aphasia using EEG-based neural envelope tracking of natural speech

Abstract: After a stroke, approximately one-third of patients suffer from aphasia, a language disorder that impairs communication ability. The standard behavioral tests used to diagnose aphasia are time-consuming, require subjective interpretation, and have low ecological validity. As a consequence, comorbid cognitive problems present in individuals with aphasia can bias test results, generating a discrepancy between test outcomes and everyday-life language abilities. Neural tracking of the speech envelope is a promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 83 publications
3
16
0
1
Order By: Relevance
“…Once neural tracking in aphasia is better understood, the application potential of this method could be manifold. A study that is currently in preparation found that IWA can be distinguished from healthy controls with 83% accuracy based on neural envelope tracking with mutual information of only 5 to 7 minutes of EEG data (De Clercq et al, 2023). Looking a step further into the future, an aphasia diagnosis based on processing levels of different speech representations could complement behavioral diagnosis and inform speech-language pathologists further which functions should be trained in therapy.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…Once neural tracking in aphasia is better understood, the application potential of this method could be manifold. A study that is currently in preparation found that IWA can be distinguished from healthy controls with 83% accuracy based on neural envelope tracking with mutual information of only 5 to 7 minutes of EEG data (De Clercq et al, 2023). Looking a step further into the future, an aphasia diagnosis based on processing levels of different speech representations could complement behavioral diagnosis and inform speech-language pathologists further which functions should be trained in therapy.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Moreover, the method could be useful in the acute phase after stroke, when behavioral diagnostic tests are too exhausting for patients. This would still have to be tested in a clinically more compatible experimental setting in the future, but work by De Clercq et al (2023) shows that only few minutes of recording time would be needed to get reliable data. Additionally, articulatory speech representations (e.g., mouth aperture, tongue protrusion (Mitra et al, 2010)) could be investigated to analyze effects of production impairments in aphasia during listening.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…In response to narratives, individuals with post-stroke aphasia (IWA) display decreased neural tracking of the envelope and linguistic speech representations (Kries et al, 2023a;De Clercq et al, 2023a, 2024b. Neural tracking measures further predicted aphasia at the individual level (De Clercq et al, 2023b), with prediction accuracy almost entirely driven by envelope tracking rather than linguistic tracking (De Clercq et al, 2024b). These findings may suggest a role for envelope tracking in language-related processes, given its ability to detect a language disorder through reduced envelope tracking measures.…”
Section: Introductionmentioning
confidence: 96%
“…Among various disorders, neural tracking has found application in the study of aphasia, a language disorder commonly caused by a stroke in the language-dominant left hemisphere of the brain (Papathanasiou and Coppens, 2017). In response to narratives, individuals with post-stroke aphasia (IWA) display decreased neural tracking of the envelope and linguistic speech representations (Kries et al, 2023a;De Clercq et al, 2023a, 2024b. Neural tracking measures further predicted aphasia at the individual level (De Clercq et al, 2023b), with prediction accuracy almost entirely driven by envelope tracking rather than linguistic tracking (De Clercq et al, 2024b).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existing evidence of neural envelope tracking as a biomarker for diverse language disorders, [21][22][23][24] research on post-stroke aphasia to date remains limited. In our most recent works, we used temporal response functions (TRF) 25 and temporal mutual information functions (TMIF) 26,27 as measures of neural tracking. The first consists of a linear model, where weights represent the amplitude of the brain response to the stimulus at different latencies; the latter is a statistical approach also capturing non-linear relationships between the EEG and the stimulus, and provides a more thorough assessment of neural tracking.…”
Section: Introductionmentioning
confidence: 99%